PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT BANK MANDIRI SYARIAH CABANG FANINDO - Rizal, Muhammad; Efnita, Titik (SCIENTIA JOURNAL, 2019)
This study aims to analyze the influence of product quality and service quality on customer satisfaction at Fanindo PT Bank Mandiri Syariah Branch. This research was conducted at PT Bank Mandiri Syariah Fanindo Branch which is located at Fanindo shop F Block No. 5-6. The sample in this study amounted to 100 people taken using probability sampling techniques with random sampling method. Data collection is done by distributing questionnaires using a 5-point Likert scale to measure 15 indicators. This research uses data analysis method using SPSS version 21 software with the name IBM SPSS Statistics 21. The analytical tool used is multiple linear analysis, hypothesis testing using T test and F test. And first test result hypothesis is produc quality partial effect on customer satisfaction. The second hypothesis i that service quality has a partial effect on customer satisfaction. The third hypothesis is product quality and service quality simultaneously or jointly influence the satisfaction of the customers of PT Bank Mandiri Syariah Fanindo Branch.